Bones around town: Taphonomic patterns from civic feasting and residential dining contexts at Late Archaic Azoria, Crete. (April 2021) - Dibble, Flint
Highlights: Contextual taphonomic approach to zooarchaeological material from Azoria. Taxonomy and mortality show same animals consumed in feasts and at home. Feasts can be distinguished from residential meals through butchery methods. Cleaver chops at civic feasts show the efficiency of professional butchers. Structured deposits of burned bones reveal an abandonment sacrificial ritual. Abstract: This paper evaluates the contextual taphonomy of faunal material from Azoria, Crete. The sudden abandonment of the settlement around 480 B.C.E., provides a rich archaeological record to understand the use of space across the site. In particular, the excavation of large civic dining complexes and smaller town houses enables a comparison of residential and civic dining practices. The standard set of evidence usually included in zooarchaeology reports – taxonomic composition and mortality profiles – are similar across the settlement, indicating that largely the same animals of similar ages were consumed in houses and at civic feasts. However, traces from taphonomic processes expose the differential use of space across the settlement. Bones with cleaver-chops found in the large Communal Dining Building reveal different cuts of meat were consumed at residential meals versus civic feasts. The scale of these feasts is also seen in an increased frequency of gnawed bones found in the kitchens of the same building, suggesting that even the local pets enjoyed the glut of meat from a civic feast. A final, ritual meal taken by the inhabitants of Azoria before abandoning the settlement is uncovered from structured deposits of burned bones.